Productivity of dairy cows supplemented with silage of fava bean or fodder beet - Nieto-Sierra, David Felipe (2020)
Introduction. Milk production systems are affected by climate change, presenting seasonality in forage production, and added to this, breeds with high nutritional requirements predominate, which leads producers to permanently use concentrates that increase the costs of production. Objective. The objective of this work was to evaluate milk production and quality in cows supplemented with espadrille bean (Vicia faba L.) and fodder beet (Beta vulgaris L.) silage. Materials and methods. The study was conducted at the Obonuco Research Center of AGROSAVIA, municipality of Pasto, Nariño, Colombia. Twelve cows of the F1 breed (Kiwi Cross X Holstein) were used, of first childbirth (93 days of breastfeeding), with an average live weight of 460 kg. Cows were kept in paddocks with grasses, legumes, and water ad libitum. For three periods of fifteen days each, three levels of silage inclusion (0, 4 and 8 kg day-1) of bean and beet were evaluated, using a 3x3 Latin square experimental design for each species. Daily production of each animal was recorded and the compositional quality of the milk (fat, protein, total solids and milk urea nitrogen MUN) was determined. Results. With the highest level of inclusion (8 kg cow-1 day-1), the alpargata bean silage had an effect (p<0.05) on the protein percentage, while the fodder beet silage influenced (p<0,05) in the percentage of fat. Both species did not influence production, total solids, and MUN. Conclusion. The supply of bean and beet silage influenced the compositional quality of milk, providing food alternatives in the milk production systems of the upper tropics of Nariño, allowing seasonality and the replacement of common sources to be reduced.